(untitled) (Encuentros, 2024)
The article studied the School of Salamanca and the Christian Humanism in the formation of students entrepreneurs in Palmira, Valle del Cauca. The School developed a very important work of public and private management in America until the collapse of the Spanish Empire. The study was descriptive, mixed, historicist, worked with a sample of 41 students, collected general, personal and managerial information to determine the roots in the students of the principles of Christian Humanism, Salamanca heritage. The prevailing personal and managerial variables such as tolerance, recognition, solidarity, dignity, ethics, dialogue, humanism, generosity, magnificence and common good, correspond to the Salamanca legacy and Christian Humanism. It was concluded about the importance of humanistic training, which could exceed the Anglo-Saxon utilitarian management model.